METHODS USED IN PRIMARY CLASS MOTHER LANGUAGE LESSONS (Academia Science Repository, 2023)
This article provides information about the methods used in primary school mother tongue classes. Until the last years of the 19th and 20th centuries, explanatory method, conversational method, analysis-synthesis method, independent work method, inductive and deductive methods were used more in mother tongue teaching. In recent years, world didactics have carried out considerable scientific research on educational methods and their classification.